2007
DOI: 10.1177/1545968306298932
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Electrical Stimulation Versus Volitional Isometric Strength Training in Children With Spastic Diplegic Cerebral Palsy: A Preliminary Study

Abstract: Background-To date, no reports have investigated neuromuscular electrical stimulation (NMES) to increase muscle force production of children with cerebral palsy (CP) using high-force contractions and low repetitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(114 citation statements)
references
References 59 publications
2
110
2
Order By: Relevance
“…
N euromuscular electrical stimulation (NMES) is a promising tool in the rehabilitation of individuals with a limited ability to activate their skeletal muscles, 13,35,36 as well as a method of strength training and short-term resistance training in athletic populations. 26,27 During NMES application, the capacity to maintain performance is compromised compared to voluntary exercise, Experimental laboratory study.

The primary purpose was to investigate the independent effects of current amplitude, pulse duration, and current frequency on muscle fatigue during neuromuscular electrical stimulation (NMES).

…”
mentioning
confidence: 99%
“…
N euromuscular electrical stimulation (NMES) is a promising tool in the rehabilitation of individuals with a limited ability to activate their skeletal muscles, 13,35,36 as well as a method of strength training and short-term resistance training in athletic populations. 26,27 During NMES application, the capacity to maintain performance is compromised compared to voluntary exercise, Experimental laboratory study.

The primary purpose was to investigate the independent effects of current amplitude, pulse duration, and current frequency on muscle fatigue during neuromuscular electrical stimulation (NMES).

…”
mentioning
confidence: 99%
“…2,4 Force responses were elicited using trains of electrical stimuli with different stimulus patterns (i.e. CFTs, VFTs, and DFTs; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…6 A recent study revealed that high-intensity electrical stimulation is more effective in producing gains in strength and walking velocity than voluntary isometric exercise. 4 Electrical stimulation generated higher forces and maintained greater average force throughout exercise than volitional effort, which is affected by impaired activation. One emerging intervention for individuals with CP is FESassisted cycling 7 to improve coordination and to increase power output and exercise intensity for cardiovascular fitness training.…”
Section: Cftmentioning
confidence: 99%
See 2 more Smart Citations